Customer Intimacy in Mobile Retail - Míček, Martin (2010)
The master thesis deals with the topic of customer intimacy in mobile telecommunications and describes how the concept of a value-based strategic approach called "customer intimacy" can be applied in telecommunications industry, illustrated on an example of a mobile operator customer relationship lifecycle model. The goal of the thesis is to evaluate mobile telecommunications industry potential for application of the value discipline of customer intimacy and illustrate a high-level framework of Customer Lifecycle Management model as the first transformational step towards customer-intimate organizational design. The thesis sets main hypothesis on the assumption that adoption of the strategy and principles of customer intimacy enable a mobile operator to capture ownership of positive customer experience and secure a sustainable competitive advantage, thereby presenting a powerful counter-measure against the zero-growth industry outlook. As a sub-hypothesis the author postulates the statement that CLM infuses highly-effective methods to capture additional customer value and positively affect mobile operators' profitability. The theoretical part defines characteristics and components of customer value in business relationships and describes truths featuring the new world of competition. This new paradigm of competition leads to the definition of rules for delivering superior value in the following subchapter. Consequently, three value-based strategic approaches towards market leadership (denoted as "value disciplines") are identified and characterized. The second part presents the goals and key principles of the value discipline of customer intimacy and adverts to distinctions in theory and business practice. The author identifies forces driving strategic initiatives focusing on customer value perception and expectations. In this part the opportunities for adoption of customer intimacy in consumer telecommunications industry are also assesses.